Book Reviews. Issue 1 (1st March 2019) - Jones, Ryan T.; Bara, Anna; Grosheva, Galina V; Gruzdeva, Ekaterina; Schweitzer, Peter; Demps, Kathryn; Laptander, Roza
Abstract : A World Trimmed with Fur: Wild Things and the Natural Fringes of Qing Rule Jonathan Schlesinger (Stanford, CA: Stanford University Press, 2017), 288 pp. ISBN: 9780804799966 Ethnic and Religious Minorities in Stalin's Soviet Union: New Dimensions of Research Andrej Kotljarchuk and Olle Sundström, eds. (Stockholm: Elanders, 2017), 283 pp., paperback 27.00. ISBN: 978-91-7601-777-7. Kosmologiia i praktika sibirskogo shamanizma Elena V. Nam (Tomsk: Tomskii gosudarstvennyi universitet, 2017), 296 pp. ISBN: 978-5-7511-2521-9. Kul'tura i resursy. Opyt etnologicheskogo obsledovaniia sovremennogo polozheniia narodov Severnogo Sakhalina Dmitrii Funk, ed. (Moscow: "Demos, " 2015), 272 pp. ISBN 978-5-9904710-6-1. Maritime Hunting Culture of Chukotka: Traditions and Modern Practices Igor Krupnik and Rachel Mason, eds. (Anchorage, AK: National Park Service, Shared Beringian Heritage Program, 2016), 343 pp. ISBN: 9780990725251. Litsom k moriu: Pamiati Liudmily Bogoslovskoi Igor Krupnik, ed. (Moscow: Moskva, 2016), 647 pp. ISBN 9785600013650. T-Bone Whacks and Caviar Snacks: Cooking with Two Texans in Siberia and the Russian Far East Sharon Hudgins (Denton: University of North Texas Press, 2018), 448 pp. ISBN: 9781574417142. Bij de Joekagieren. Het oudste toendravolk van Noord-Oost Siberië / Life with the Yukaghir: Northeast Siberia's Oldest Tundra People Cecilia Odé (Lias, Uitgeverij: Verschijningsjass, 2018), 240 pp., €29.95 (paperback). ISBN: 978-90-8803-099-4.